1983
DOI: 10.1007/bf02308080
|View full text |Cite
|
Sign up to set email alerts
|

Control of experimental massive periretinal proliferation by daunomycin: dose-response relation

Abstract: A condition similar to massive periretinal proliferation in man can be produced in rabbits by injecting homologous fibroblasts into the vitreous. We have studied the effect of daunomycin, a cytotoxic drug, in this model to determine a dose which would not be toxic to the retina but would be effective in preventing proliferation of the injected fibroblasts and eventual retinal detachment. The results of this study demonstrate that daunomycin at a dose of 9 nmol per eye reduces the incidence of retinal detachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…They concluded that DNR seemed to be effective to suppress reproliferation, but that care should be taken to avoid postoperative complications. 9,[22][23][24][25] Some workers 10,11 have performed research into use of DNR as an agent for preventing PCO. They noted that DNR could effectively inhibit the proliferation of human lens epithelial cells in vitro at the concentration of 0.5 mg/ml, almost reaching the greatest effect at the concentration of 7.5 mg/ml.…”
Section: Daunorubicinmentioning
confidence: 99%
“…They concluded that DNR seemed to be effective to suppress reproliferation, but that care should be taken to avoid postoperative complications. 9,[22][23][24][25] Some workers 10,11 have performed research into use of DNR as an agent for preventing PCO. They noted that DNR could effectively inhibit the proliferation of human lens epithelial cells in vitro at the concentration of 0.5 mg/ml, almost reaching the greatest effect at the concentration of 7.5 mg/ml.…”
Section: Daunorubicinmentioning
confidence: 99%
“…Various antiproliferative drugs were sug gested as possible alternatives to 5-FU ad ministered intravitreally in order to prevent P V R , such as daunomycin [8] and Taxol [9]. Among other parameters, evaluation o f the effect o f any drug to be suggested as an alter native should be compared to the effect of 5-FU or its sustained-release analogue, when the treated eyes (by 5-FU) and the control eyes were in different animals, as recom mended.…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous studies have shown that the anthracycline drug DNR is effective in inhibiting PVR formation. 23,24 Unfortunately, DNR has a short half-life in the eye vitreous coupled with a narrow therapeutic concentration range, thus requiring frequent injections over time. 25 Therefore, a sustained delivery system is needed to control the drug release within its therapeutic window.…”
Section: Introductionmentioning
confidence: 99%